Amazon's Three Major Lines of Business - Edward A. Snyder; Jason Canaday; Marley Hughes (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
Since its founding in 1995 Amazon has become a leader in eCommerce, cloud computing services, and interactive devices for individuals and homes. In this study, we document the critical steps in Amazon's development in each line of business. Our review yields insights on (i) how Amazon responded to changes in demand, (ii) the importance of economies of scale, economies of scope, and network effects in Amazon's efforts to build out its lines of business, and (iii) interrelationships among these three apparently distinct commercial operations. This case study thereby provides insights how Amazon's Firm Specific Advantages (FSAs) contributed to its successes within and across lines of business. Our analysis further suggests that Amazon developed Dynamic Capabilities (DCs) capabilities that contributed to Amazon's superior performance. Our analysis is, however, necessarily interim in nature. Given changing market and regulatory conditions, whether Amazon will be able to sustain its performance in which lines of business and in which countries is uncertain.
Keywords: L26; L7; L86; M21; 330; entrepreneurship and business strategy; transaction cost economics; market entry; market power; dynamic capabilities; firm specific advantages